2022
DOI: 10.1038/s41598-022-26894-5
|View full text |Cite
|
Sign up to set email alerts
|

An exosome-related long non-coding RNAs risk model could predict survival outcomes in patients with breast cancer

Abstract: Breast cancer (BC) is one of the most frequent malignancies among women worldwide. Accumulating evidence indicates that long non-coding RNA (lncRNA) may affect BC progression. Exosomes, a class of small membrane vesicles, have been reported to promote tumor progression through transporting proteins, mRNAs, lncRNAs and some other small molecules. However, the interaction between exosome-related lncRNAs and the microenvironment of malignancies is unclear. Hence, we proceeded to investigate the relationship betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Cancer immunotherapy mainly exerts either active stimulation of the immune system by vaccination or adoptive immunotherapy by cell therapy such as TIL, nature killer cells, cytokine-induced peripheral blood mononuclear cells (lymphokine-activated killer, LAK; cytokine-induced killer cells, CIK; dendritic cells and cytokine-induced killer cells, DC-CIK), neutrophil and macrophage [56][57][58][59][60] . According to published evidence, TILs obtained from tumor tissues with a higher population of CD8 cells, but they also have other immune cells, such as T-cell, B-cell, NK cells, macrophage, and neutrophil [61][62][63][64][65][66][67][68] .…”
Section: Experimental Results On the New Modulementioning
confidence: 99%
“…Cancer immunotherapy mainly exerts either active stimulation of the immune system by vaccination or adoptive immunotherapy by cell therapy such as TIL, nature killer cells, cytokine-induced peripheral blood mononuclear cells (lymphokine-activated killer, LAK; cytokine-induced killer cells, CIK; dendritic cells and cytokine-induced killer cells, DC-CIK), neutrophil and macrophage [56][57][58][59][60] . According to published evidence, TILs obtained from tumor tissues with a higher population of CD8 cells, but they also have other immune cells, such as T-cell, B-cell, NK cells, macrophage, and neutrophil [61][62][63][64][65][66][67][68] .…”
Section: Experimental Results On the New Modulementioning
confidence: 99%
“…In comparison, a distinct study [ 64 ] focused on short-term outcomes reported AUCs of 0.68, 0.745, and 0.714 for 100, 200, and 300 days, emphasizing the variability in predictive timelines. Another research [ 65 ] showed promising long-term predictions for 2, 3, and 5 years with AUCs of 0.727, 0.691, and 0.695, while a further study [ 66 ] validated its risk score for breast cancer survival over similar periods, achieving AUCs of 0.714, 0.676, and 0.729. Our model's focus on longer-term predictions aligns better with clinical needs in breast cancer, emphasizing its utility in providing meaningful prognostic insights.…”
Section: Discussionmentioning
confidence: 99%
“…Serum exosomal lncRNA XIST has been described as a potential biomarker to diagnose TNBC recurrence [ 477 ]. Fifteen exosome-related differentially expressed lncRNAs were recently identified to be correlated with BC prognosis [ 478 ].…”
Section: Exosomes As Relevant Breast Cancer Biological Markersmentioning
confidence: 99%